The collision of patagonia: Geological facts and speculative interpretations - Ramos, Victor Alberto; Lovecchio, Juan Pablo; Naipauer, Maximiliano; Pángaro, Francisco (Ameghiniana)
The Paleozoic evolution of Patagonia was the focus of controversies between its allochthonous or autochthonous origin. The arrival of plate tectonics supported new allochthonous alternatives and from an initial fixist resistance, different mobilistic hypotheses have made their way. There is currently some consensus about its allochthony, but there is no agreement on collision times or in the configuration of the continental blocks involved. Based on the present data an alternative is developed that fits better with existing information. The northeastvergent deformation in Ventania System, the Hespérides Basin, its wide longitudinal and transverse distribution, show that collision occurred in the northern sector of Northern Patagonian Massif, and extended through the southern African Gondwanides. Their similar metamorphic and tectonic patterns identified a previous southward subduction with a Permian climax, characteristic of a continent-continent collision. The associated magmatic arc has been partially obliterated by slab-breakoff and delamination in the Late Permian–Triassic. The western magmatic belt along the Pacific margin is older, spanning from Devonian to mid-Carboniferous. The Chaitenia island arc collision in Upper Devonian produced an episode of exhumation and uplift. This western belt extends into Tierra del Fuego island and its contour allows tentatively to recognize a Southern Patagonian terrane. It is speculated that this block may have included the Antarctic Peninsula, although more data is needed to characterize its composition and areal development. However, it is concluded that the dimensions of this southern terrane cannot justify the broad regional deformation of the Gondwanides. Fil: Ramos, Victor Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo ...